Finite Element Analysis of Contra Bass Bridge - Nurul Fatin Syazwani Binti Azman, Nurul Fatin Syazwani (Universiti Teknologi Petronas, 2012)
Double bass is a string type instrument that has been evolved each generation due to the increased demand for better quality sound. A lot of amplifiers and transducers were used to transferring and amplifying the original sound of the contra bass but the most important is to maintain its original acoustic timbre of wood-bass characteristics. The main objective of this project is to determine stress concentration area on the bridge of contra bass in the proportion to propose the best mounting position of the sound transducer. Based on author’s research and background study in FYP I, the acoustic timbre characteristic would be improved by embedded the sensor at the location on the bridge with maximum stress concentration. To determine the location, the author has chosen Finite Element Analysis using ANSYS among some available methods due to its high feasibility. CATIA: Sketch Tracer also being used in conjunction with ANSYS in the development of the bridge solid modeling. Stress concentration area on the bridge was successfully determined at the end of the project and all related analysis, results and discussion had been compiled in the thesis.